Synergistic association of resveratrol and histone deacetylase inhibitors as treatment in amyotrophic lateral sclerosis - Parrella, Edoardo; Porrini, Vanessa; Scambi, Ilaria; Gennari, Michele M.; Gussago, Cristina; Bankole, Oluwamolakun; Benarese, Marina; Mariotti, Raffaella; Pizzi, Marina (Frontiers in Pharmacology, 2022)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease associated with motor neuron degeneration, progressive paralysis and finally death. Despite the research efforts, currently there is no cure for ALS. In recent years, multiple epigenetic mechanisms have been associated with neurodegenerative diseases. A pathological role for histone hypoacetylation and the abnormal NF-κB/RelA activation involving deacetylation of lysines, with the exclusion of lysine 310, has been established in ALS. Recent findings indicate that the pathological acetylation state of NF-κB/RelA and histone 3 (H3) occurring in the SOD1(G93A) murine model of ALS can be corrected by the synergistic combination of low doses of the AMP-activated kinase (AMPK)-sirtuin 1 pathway activator resveratrol and the histone deacetylases (HDAC) inhibitors MS-275 (entinostat) or valproate. The combination of the epigenetic drugs, by rescuing RelA and the H3 acetylation state, promotes a beneficial and sexually dimorphic effect on disease onset, survival and motor neurons degeneration. In this mini review, we discuss the potential of the epigenetic combination of resveratrol with HDAC inhibitors in the ALS treatment.